Facing a world in crisis: what life teaches us in challenging times / edited by David Skitt - "Krishnamurti, J" (Chennai, 2007)
If ever we are to understand ourselves, says Krishnamurti, we must look at the state of the world, with all its violence and conflict. To turn away from world events is for him not to be alive to what life has to teach us. Facing a World in Crisis presents a selection of talks that Krishnamurti gave on how to live and respond to troubling and uncertain times. His message of personal responsibility and the importance of connecting with the broader world is presented in a non-sectarian and non-political way. Direct and ultimately life-affirming, this book will resonate with readers today who are looking for a new way to understand and find hope in challenging times. Part One of the book consists of seven talks that Krishnamurti gave in Saanen, Switzerland, in 1972. Part Two contains, edited and slightly abridged, the last four talks and two question-and-answer sessions he held in England in 1985."
Keywords: Conduct of life